Their Plea for Freedom – Their Flight from Home: Jewish Women’s Quest for Education, Love, and Anarchism - Rabinovich Irina; Gasztold Brygida (American, British and Canadian Studies Journal)
This article presents a comparative analysis of how Jewish American writers Rosa Sonneschein and Wilhelmina Wittigschlager, the American writer Kendrick Belle Abbot, and the Polish Jewish writer Aniela Kallas portray young Jewish women who escape their homes. The study delves into both the literal acts of escape and the deeper, internal struggles for spiritual and personal freedom experienced by these women. Unlike most existing research that examines the “runaway daughters” phenomenon through a historiographical approach, our study innovatively revives the voices of both fictional characters and the real female Jewish writers behind them. By focusing on these narratives, this article reveals a significant shift in how young Jewish women are represented. Historically objectified, these figures are increasingly depicted as self-assertive and autonomous individuals. The analysis not only highlights this evolution in representation but also contributes to our understanding of the broader cultural and ideological changes at play. The novels in question illustrate a transformative shift from viewing young Jewish women as mere subjects of their circumstances to recognizing them as proactive agents in their own stories. This change is indicative of a deeper cultural rethinking, where women reclaim their agency and redefine their roles within their communities, challenging traditional norms and expectations.